2008
DOI: 10.1080/17458080802603715
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and optical properties of poly(methyl methacrylate)/calcium carbonate nanocomposite

Abstract: The study deals with thermal and optical properties of poly(methyl methacrylate) (PMMA) containing 2wt% calcium carbonate (CaCO 3 ) nanofiller. It was found that the thermal conductivity increases with increasing temperatures, due to thermal activation of the phonons in the PMMA/CaCO 3 nanocomposite. This enhancement in the thermal conduction is mainly attributed to the heat transferred by lattice vibrations as major contributors and electrons as minor contributors during thermal conduction. The optical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Similar to the studies in the literature, the indirect transition energies ( E i ) were obtained lower than the direct transition energies ( E d ) . In literature, the studies on various PMMA composites have reported that the optical band gap energy is in the range of 3.0–5.5 eV for pure PMMA , and the band gap energy level of insulating materials is around 6 eV. As pure PMMA is an insulating polymer, the value of 6 eV obtained is an acceptable result.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Similar to the studies in the literature, the indirect transition energies ( E i ) were obtained lower than the direct transition energies ( E d ) . In literature, the studies on various PMMA composites have reported that the optical band gap energy is in the range of 3.0–5.5 eV for pure PMMA , and the band gap energy level of insulating materials is around 6 eV. As pure PMMA is an insulating polymer, the value of 6 eV obtained is an acceptable result.…”
Section: Resultssupporting
confidence: 80%
“…While this increment is linear for R 6 wt% , it has an exponential character for R 10 wt% . It has previously been reported that the E U values are increased by increasing the amount of conductive additive for various PMMA composite systems . E U is also a measure of amorphousness .…”
Section: Resultsmentioning
confidence: 99%
“…This edge is a measure of the optical BG energy [ 36 , 37 ]. The extent of absorption is based on an absorption coefficient α ( υ ), indicating the relative rate at which the incident light intensity attenuates in a unit length of the medium [ 11 , 38 , 39 ]. Determination of the ( υ ) at the equivalent frequency (υ) from the absorbance spectra A ( υ ) can be performed using Beer–Lambert law [ 6 , 36 , 37 ]: where the incident light and transmitted light intensities are denoted by I o and I, respectively, and the sample thickness is represented by d. Figure 5 shows α ( υ ) against photon energy ( hυ ) for pure PVA and PVA films doped with CeO 2 samples.…”
Section: Resultsmentioning
confidence: 99%
“…Table V shows the variation of the thermal conductivity with temperature for the 20 wt % iron composite on heating to about 50°C. It can be seen that conductivity increases with temperature from a value 0.20 to 0.26 W/m °C in a small temperature rise of 5°C, which is due to thermal activation of the phonons in the composite 20. In heating, phonons, electrons, and impurities are activated and thus enhance the thermal conductivity of the polymeric composites.…”
Section: Resultsmentioning
confidence: 97%